2021
DOI: 10.1002/ijc.33529
|View full text |Cite
|
Sign up to set email alerts
|

Adequate asparaginase is important to prevent central nervous system and testicular relapse of pediatric Philadelphia chromosome‐negative B‐cell acute lymphoblastic leukemia

Abstract: Asparaginase (Asp) is one of the most important drugs for treating acute lymphoblastic leukemia (ALL). However, off‐protocol Asp administration (OPAA) or hypersensitivity may disturb its pharmacokinetic profile. In this retrospective study, we sought to determine whether OPAA and hypersensitivity to Escherichia coli asparaginase (E coli Asp) impaired extramedullary relapse prevention in a pediatric ALL cohort treated according to SCMC‐ALL‐2005 protocol from 2005 to 2014 at the Shanghai Children's Medical Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While it is well established that systemic asparaginase lowers asparagine levels in the CNS, it is uncertain whether this provides any additional benefit to prevent CNS dissemination 43 . Recent paediatric studies have reported discordant results 44,45 . In our series, all patients received asparaginase: further analyses on the doses administered and interruptions are warranted.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…While it is well established that systemic asparaginase lowers asparagine levels in the CNS, it is uncertain whether this provides any additional benefit to prevent CNS dissemination 43 . Recent paediatric studies have reported discordant results 44,45 . In our series, all patients received asparaginase: further analyses on the doses administered and interruptions are warranted.…”
Section: Discussionmentioning
confidence: 81%
“…43 Recent paediatric studies have reported discordant results. 44,45 In our series, all patients received asparaginase: further analyses on the doses administered and interruptions are warranted.…”
Section: Discussionmentioning
confidence: 95%
“…In present protocol, we speculated that adequate and effective treatment with pediatricinspired regimen could induce durable remission to avoid early relapse, and subsequently spare enough time to reconstitute the immune system to exert GVL effect. Furthermore, the importance of a su cient dose of asparaginase for better survival in AYA ALL has been widely accepted, with patients received more than 20 weeks of asparaginase showing better survival compared to those with a lower cumulative dose [37][38][39][40] . Based on these studies, we scheduled allo-HSCT after 4 blocks of consolidation therapy, ensuring patients receive a su cient dose of asparaginase and achieve a deeper remission.…”
Section: Discussionmentioning
confidence: 99%